Investigation of the mechanical and forming behaviour of 3D warp interlock carbon woven fabrics for complex shape of composite material. Issue 3 (June 2022) - Korkmaz, Mehmet; Okur, Ayşe; Labanieh, Ahmad Rashed; Boussu, François
Composite materials which are reinforced with 3D warp interlock fabrics have outstanding mechanical properties such as higher delamination resistance, ballistic damage resistance and impact damage tolerance by means of their improved structural properties. Textile reinforcements are exposed to large deformations in the production stage of composite materials which have complex shape. Although good formability properties of 3D warp interlock fabrics in forming process were already proven by recent studies, further information is needed to elucidate forming behaviours of multi-layer fabrics which is produced with high stiffness yarns like carbon. In this study, 3D warp interlock carbon fabrics were produced on a prototype weaving loom and the same carbon yarn was used in two fabric directions with equal number of yarn densities. Fabrics were differentiated with regard to the presence of stuffer warp yarn, weave pattern and parameters of binding warp yarn which are angle and depth. Therefore, the effect of fabric architecture on the mechanical and formability properties of 3D warp interlock carbon fabrics could be clarified. Three different breaking behaviours of fabrics were detected and they were correlated with crimp percentages of yarn groups. In addition, the bending and shear deformations were analysed in view of parameters of fabric architectures. Two distinct forming behaviours of fabrics were determined according to the distribution of deformation areas on fabrics. Moreover, the optimal structure was identified for forming process considering the fabric architecture.